A biochemical, theoretical and immunohistochemical study comparing the therapeutic efficacy of curcumin and taurine on T-2 toxin induced hepatotoxicity in rats - Al-Zahrani, Maryam H.; Balgoon, Maha J.; El-Sawi, Nagwa M.; Alshubaily, Fawzia A.; Jambi, Ebtihaj J.; Khojah, Sohair M.; Baljoon, Raghad S.; Alkhattabi, Nuha A.; Baz, Lina A.; Alharbi, Asmaa A.; Ahmed, Amira M.; Abo elkhair, Ayat M.; et al. (Frontiers in Molecular Biosciences, 2023)
Foodborne trichothecene T-2 Toxin, is a highly toxic metabolite produced by Fusarium species contaminating animal and human food, causing multiple organ failures and health hazards. T-2 toxins induce hepatotoxicity via oxidative stress causing hepatocytes cytotoxicity and genotoxi-city. In this study, curcumin and taurine are investigated and compared as antioxidants against T-2-provoked hepatotoxicity. Methods: Wistar rats with T-2 toxin sublethal oral dose (0.1mg/kg) for two months, followed by curcumin (80 mg/kg) and taurine (50mg/kg) for three weeks. Bio-chemical assessment of liver enzymes, lipid profiles, thiobarbituric acid reactive substances (TBARs), AFU, TNF-α, total glutathione, molecular docking, histological and immunohisto-chemical markers for anti-transforming growth factor-β1 (TGFβ1), double-strand DNA dam-age(H2AX) , regeneration (KI67) and apoptosis (Active caspase3)was done. Results: Compared to T-2 toxin, curcumin and taurine treatment significantly ameliorated hepatoxicity as; hemoglobin, hematocrit and glutathione, hepatic glycogen, and KI-67 immune-reactive hepatocytes were sig-nificantly increased. Although, liver enzymes, inflammation, fibrosis, TGFβ1 immunoexpressing and H2AX and active caspase 3 positive hepatocytes were significantly decreased. Noteworthy, curcumin's therapeutic effect was superior to taurine by histomorphometry parameters. Fur-thermore, molecular docking of the structural influence of curcumin and taurine on the DNA sequence showed curcumin's higher binding affinity than taurine. Conclusion: Curcumin and taurine have a potent antioxidative effect against T-2 hepatotoxicity with more effectiveness for curcumin.